Synthesis, Characterization, ADME, Molecular Docking, In Silico Structural and Mechanistic Studies and Biological Activities of Pt(IV) Complexes Based on Diamine Derivatives - Majeed, Sattar R.; Amin, Mina A.; Goren, Hasan Yavuz; Dedeoglu, Burcu; Attaby, Fawzy A.; Soliman, Ahmed A. (Wiley, 2025)
Pt(IV) complexes based on diamine derivatives, 3,4-diaminobenzoic acid (DABA), and 4-chloro-o-phenylenediamine (CPDA) were prepared and investigated thermally, spectroscopically, and magnetically. Thermal investigations revealed that the octahedral complexes were thermally stable. DFT calculations confirmed that the calculated absorption and infrared data agreed with the experimental results. Hydrolysis and reduction mechanisms were also investigated computationally to assess the activation behavior of the complexes. Hydrolysis barriers indicated substantial kinetic inertness, while reduction via enolate beta-carbon attack was found to be energetically accessible under physiological conditions. The potential cytotoxicity of the complexes was screened against HELA, PC3, and MCF7. [Pt (CPDA)(ox)Cl2] showed activity against the HELA cancer cell line with IC50 values of 14.9 mu g/mL. The complexes also exhibited antibacterial activities against Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus. The highest antibacterial activity was observed against S. aureus, with the complexes demonstrating performance comparable to that of the standard; [Pt (CPDA)Cl4] exhibited an inhibition zone with diameters of 23.6 +/- 0.6 mm. Docking studies were conducted against E. coli (PDB ID: 6F86) and S. aureus (PDB ID: 3q89). ADME investigations were carried out to study the absorption and metabolism properties of the Pt(IV) complexes.
Keywords: biological activities; DFT; docking; hydrolysis; Pt(IV); reduction